2016
DOI: 10.1038/bjc.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Clinical impact of mutation fraction in epidermal growth factor receptor mutation positive NSCLC patients

Abstract: Background:We examined clinical outcomes in a population-based cohort of EGFR mutant advanced NSCLC patients, exploring the potential role of factors including tumour EGFR mutation fraction and cellularity in predicting outcomes.Methods:A cohort of patients with EGFR mutant advanced NSCLC was identified (N=293); clinical outcomes, pathologic and treatment details were collected. Tumour response was determined from radiology and clinical notes. Association between demographic and pathologic variables EGFR TKI r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…To date, >30 mutations of EGFR have been reported, including 19-Del (~45% all EGFR mutations), L858R (~40–45%), G719X (~5%), 20-Ins (~1%) ( 5 , 12 , 21 ). Studies have suggested that EGFR mutation rates in patients with lung adenocarcinoma differ among countries and ethnicities, between sexes, and with smoking status ( 25 27 ). The overall mutation rate of EGFR in Chinese patients with lung adenocarcinoma in the present study was 50.7%, which is consistent with previous reports ( 6 , 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To date, >30 mutations of EGFR have been reported, including 19-Del (~45% all EGFR mutations), L858R (~40–45%), G719X (~5%), 20-Ins (~1%) ( 5 , 12 , 21 ). Studies have suggested that EGFR mutation rates in patients with lung adenocarcinoma differ among countries and ethnicities, between sexes, and with smoking status ( 25 27 ). The overall mutation rate of EGFR in Chinese patients with lung adenocarcinoma in the present study was 50.7%, which is consistent with previous reports ( 6 , 25 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have suggested that EGFR mutation rates in patients with lung adenocarcinoma differ among countries and ethnicities, between sexes, and with smoking status ( 25 27 ). The overall mutation rate of EGFR in Chinese patients with lung adenocarcinoma in the present study was 50.7%, which is consistent with previous reports ( 6 , 25 27 ). The mutation rate in female patients was significantly higher than that of male patients (P<0.001) while the mutation rate in smokers was low compared with non-smokers (P=0.003), which was also consistent with previous reports ( 25 , 26 , 28 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, our results did not reveal such emergence of RAS mutations in metastatic lesions, possibly due to small sample size. In NSCLC, higher EGFR-mutation allele frequency has been shown to correlate with response to EGFR-tyrosine kinase inhibitors 46,47 . In the event of development of appropriate targeted therapies for KRAS-mutated CRC, our results may have similar relevance.…”
Section: Discussionmentioning
confidence: 99%
“…The median progression-free survivals of patients with the ascended type of plasma L858R mutations (L858R increased to its highest level during disease progression) and the stable type (L858R maintaining stable levels during disease progression) were 11.1 (95% CI, 6.6-15.6) and 7.5 months (95% CI, 1.4-13.6), respectively, and the overall survivals (OS) were 19.7 (95% CI, 16.5-22.9) and 16.0 months (95% CI, 13.4-18.5), respectively [97]. Martin et al [98] similarly concluded that the percentages of EGFR mutations in NSCLCs have close associations with the responses to EGFR-TKI therapy, the time to treatment failure (TTF) and the OS. It is supposed that gene amplifications either facilitated the development of gene mutations or amplified their effects [99].…”
Section: Circulating Tumor Dnamentioning
confidence: 99%